Psychometric validation of the Vaccination Attitudes Examination (VAX) scale in German pre-pandemic and mid-pandemic samples - Marcel Wilhelm; Friederike L. Bender; Frank Euteneuer; Stefan Salzmann; Anne-Catherine I. Ewen; Winfried Rief (Scientific Reports)
Abstract Despite the public health value of immunizations, vaccine hesitancy is a widespread phenomenon and received special attention during the global COVID-19 pandemic. The Vaccination Attitudes Examination (VAX) Scale aims to identify anti-vaccination attitudes for understanding vaccine hesitancy. The present study is the validation of the German version of the VAX scale in pre-/mid-pandemic samples. All individuals completed an online-survey assessing prior and expected future vaccination behaviors, further constructs associated with vaccine hesitancy, as well as anti-vaccination attitudes using the translated VAX scale among others. In a first study, 297 individuals were surveyed before the COVID-19 pandemic. A second study included 260 individuals recruited during the COVID-19 pandemic. For validation, two confirmatory factor analyses have been conducted. Reliability measures (internal consistency, test–retest-correlation) were determined. The four subscales were confirmed by Confirmation Factor Analysis with a very good to excellent fit. The subscales showed good to excellent reliability and convergent validity determinants. Average VAX values significantly distinguished between individuals who had previously received or refused immunization and predicted expected vaccination behavior. The German translation of the VAX scale is effective in identifying anti-vaccination attitudes and can be used for further research on anti-vaccination attitudes and vaccine hesitancy.